Experimental infections in red-legged partridges reveal differences in host competence between West Nile and Usutu virus strains from Southern Spain - Llorente, Francisco; Gutiérrez-López, Rafael; Pérez-Ramirez, Elisa; Sánchez-Seco, María Paz; Herrero, Laura; Jiménez-Clavero, Miguel Ángel; Vázquez, Ana (Frontiers in Cellular and Infection Microbiology, 2023)
West Nile virus (WNV) and Usutu virus (USUV) are emerging zoonotic arboviruses sharing the same life cycle with mosquitoes as vectors and wild birds as reservoir hosts. The main objective of this study was to characterize the pathogenicity and course of infection of two viral strains (WNV/08 and USUV/09), co-circulating in Southern Spain, in a natural host, the Red-legged partridge (Alectoris rufa), and compare the results with those obtained with the reference strain WNV/NY99. Inoculated birds were monitored for clinical and analytical parameters (viral load, viraemia and antibodies) during 15 days post-inoculation. Partridges inoculated with WNV/NY99 and WNV/08 strains showed clinical signs such as weight loss, ruffled feathers and lethargy that were not observed in USUV/09 inoculated individuals. Although statistically significant differences in mortality were not observed, partridges inoculated with WNV strains developed significantly higher viraemia and viral loads in blood than those inoculated with USUV. In addition, viral genome was detected in organs and feathers of WNV-inoculated partridges while it was almost undetectable in USUV-inoculated ones. These experimental results indicate that the Red-legged partridge is susceptible to the assayed Spanish WNV with a pathogenicity similar to that observed for the prototype WNV/NY99 strain. By contrast, the USUV/09 strain was not pathogenic for this bird species and elicited extremely low viremia levels, demonstrating that the Red-legged partridges is not a competent host for transmission of this USUV strain.